ANALISIS KESALAHAN ARTIKULASI BAHASA INDONESIA SISWA SEKOLAH DASAR DI WAMENA: PERBANDINGAN DUA SEKOLAH DAN IMPLIKASI PEMBELAJARAN FONETIK KONTEKSTUAL - Robert Jumaikel Nusalawo; Yogi Marulitua Ambarita; Gerson Manuel; Elisabet Ida Suparyono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study analyzes patterns of Indonesian articulation errors among elementary school students in Wamena and compares findings across two schools to formulate context-specific pedagogical recommendations. Using a descriptive approach based on observational data of target-word articulations, errors were classified into substitution, distortion, elision, and epenthesis, guided by a contextual phonological framework and stakeholder interviews as the methodological design and rationale. Results from 70 students (40 from SD Lachairoi Hom-Hom; 30 from SD YPPGI Napua) show mean articulation errors per student of 3.3 (Lachairoi) and 3.1 (Napua). The most frequent patterns at both schools were /r/→/l/ substitution (9 cases at Lachairoi; 7 at Napua), /s/ distortion (five cases at each school), /k/ substitution (predominantly /k/→/g/ or /k/→/t/ at Lachairoi; notably /k/→/t/ at YPPGI Napua), elision of final –n (more frequent at Lachairoi), and epenthesis (present at both sites). The findings indicate that local first-language phonological interference strongly contributes to variation in Indonesian articulation. Accordingly, phonetic instruction grounded in local cultural knowledge and stepwise articulatory training targeting critical contrasts (/r/–/l/, /k/–/g/–/t/, fricative /s/) is recommended.